Digitalizing Notarial Practices: Law Number 2 of 2014 Study - Al Muhtar, Aman Al Muhtar; Indrati Rini (Fakultas Hukum Universitas Airlangga, 2024)
Cyber notary is proposed as a concept that can help notaries in their work more efficiently. However, problems will arise if the concept of cyber notary is linked to the UUJN which is the basis for notaries. This is what underlies this research. This research aims to evaluate the relevance of UUJN in the digital era and the Cyber notary concept. In its implementation, it will be carried out using a juridical analysis method with an approach to applicable legal regulations as a tool to conclude. It was found in the research that cyber notary cannot yet be implemented in the legal system in Indonesia because the laws governing the reading of deed contents online via video conference and digital signing are still unclear. For this reason, as a solution considering the urgency, evaluation and revision are needed to enable clear implementation of cyber notaries in Indonesia. For this reason, evaluation is needed so that notaries can serve the public more efficiently, considering the urgency of implementing cyber notary in the digital era.